Sleep duration, daytime napping, and risk of incident stroke: Nuances by metabolic syndrome from the China health and retirement longitudinal study - Fang, Yuanyuan; He, Yuqin; Huang, Yanzhu; Ran, Lusen; Song, Wenhui; Hao, Jiahuan; Yao, Di; Li, Rong; Pan, Dengji; Qin, Tingting; Wang, Minghuan (Frontiers in Cardiovascular Medicine, 2022)
Background and purpose: The relationship between sleep duration and stroke are inconclusive in China, especially in those individuals with metabolic syndrome. We aimed to investigate the association between sleep duration and incident stroke in participants with metabolic syndrome or its specific components in China. Methods: Data were taken from the 2011 and 2015 waves of China Health and Retirement Longitudinal Study (CHARLS). Habitual sleep duration (≤6, 6~8 [reference], >8 hours), daytime napping (0, 1~60 [reference], and >60 min) were determined by self-reported questionnaires. Metabolic syndrome was defined by blood assessment and biomarkers combined with self-reported doctors’ diagnosis. Incident stroke was determined by reported stroke from 2011 to 2015 wave. Cross-sectional and longitudinal associations between sleep and (incident) stroke at baseline and 4-year follow-up period were tested among the population with metabolic syndrome and its components. Results: A U-shaped relationship was observed between sleep duration and stroke in cross-sectional analysis. Sleep ≤6 hours/night had a greater risk of incident stroke (hazard ratio [HR] 1.65; 95% confidence interval [CI] 1.04-2.61) compared with sleep 6~8 hours/night. And the HR of stroke was 1.62 (95% CI, 1.03-2.53) for sleep <7 hours/day compared to 7~9 hours/day. These associations were more evident in the female and individuals aged 45 to 65 years. Furthermore, the effect of short sleep duration on incident stroke was different in each component of metabolic syndrome, which was more pronounced in participants with elevated blood pressure. And a significant joint effect of sleeping ≤6 hours/night and no napping on risk of stroke was observed (HR 1.82, 95%CI 1.06-3.12). Conclusions: Short sleep duration was an independent risk factor for incident stroke, especially among females, individuals aged 45 to 65 years, or those with some components of metabolic syndrome, such as hypertension. Napping could buffer the risk of short sleep duration on incident stroke.